Implementasi SMART Guna Pembangunan Prasarana Desa Sipaku Area - Nurul Azmi Ibrahim (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Sipaku Area Village is a village located in Simpang Empat District, Asahan Regency, North Sumatra. The existence of infrastructure in the village, namely several damaged roads caused complaints by the local community of Sipaku Area village. So that the village village agency gets the task and authority to carry out road construction in the village, a problem arises, namely where it is difficult for the village village to determine which roads will be prioritized first for repairs by the village. So to overcome these difficulties and maintain the prosperity of rural communities, especially on road infrastructure, a decision support system is needed to overcome the difficulty of selecting damaged roads to be repaired first. More efficiently, the authors designed a system known as a decision support system (DSS) by using Simple Multi Attribute Rating Technique (SMART) method which will be applied through Visual Basic and database. The coefficient of the results obtained is 0.89, this proves that the decision support system using the SMART method can be used to determine the priority of road repairs in the Sipaku village area.